A critical analysis of the adequacy of Ugandan law on protection of street children : a comparison with Islamic and Malaysian laws - Sauda, Nayiga (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2011)
This dissertation is an examination of the adequacy of Ugandan law in protecting street children. The research is done in a way of comparison with Islamic and Malaysian Law to clearly bring out the strengths and weaknesses of the Ugandan law. The study is divided into three parts. The researcher first analyses the Islamic law based on rules in the Quran and the Sunnah of the Prophet, practices of the Prophet's Companions and various opinions of the Muslim jurists. The study also includes an examination on protection of street children under various statutes and cases in Malaysia and Uganda respectively. The study proves that street children are among the most vulnerable groups of people in society. Street children are a result of social, economic, political, environmental and legal factors. They are faced with child labour, lack of food, shelter, clothing and medical care. It is evident that the street children phenomenon should be a concern to all stakeholders such as parents, judiciary, law makers, administrators and society at large not only for humanitarian reasons but because the children are the backbone of any community development and should be protected at all costs. The study also reveals that the Ugandan law on street children is in many statutes leading to difficulties in reference. It is also apparent that Islamic law has provided detailed guidelines relating to street children. Ugandan law is in line with some principles in Islamic and Malaysian law like prioritising the welfare of children and parental responsibility towards the children. The research proves that there is general lack of implementation of the available laws in Uganda. Finally the study proves that Ugandan law can still be improved for better protection of the street children. It is expected that the research will contribute to the knowledge on street children through comparing the three systems.